ANALISIS USAHA - USAHA PENJUALAN PRODUK KONVEKSI ( KASUS PEDAGANG PASAR PLAZA SUKARAMAI DI PEKANBARU) - Arista, Gita Riana; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to determine product sales businesses in Market PlazaSukaramai convection Pekanbaru and to determine obstacles in selling products onthe Market Plaza Sukaramai convection Pekanbaru . The problem formulation is Howto improve sales convection.Sales is an activity that is vital for the survival of a company , the companycertainly for a company that certainly has the ability to sell its products or productsales dipasarkanya but certainly not created by themselves , and of course, the salemust be pursued and tried to be created in order to provide income for company .Traders are people who do the trade , trade in goods that are not produced , to gain anadvantage . Merchants can be divided into wholesalers and retailers .The results showed that the population is at the Traders Market PlazaSukaramai amounted to 480 persons and the number of 20 samples taken from thename of convection in the Market Plaza Sukaramai . Sampling methods used in thestudy was purposive random sampling.Keywords : Sales , Traders , Business - Convection sales efforts